Emergence of Cronobacter sakazakii in Cases of Neonatal Sepsis in Upper Egypt: First Report in North Africa - Elkhawaga, Amal A.; Hetta, Helal F.; Osman, Naglaa S.; Hosni, Amal; El-Mokhtar, Mohamed A. (Frontiers in Microbiology, 2020)
Background and aim: Cronobacter sakazakii (C. sakazakii) has attracted considerable attention as an emerging neonatal pathogen and has been associated with outbreaks of life-threatening septicemia, necrotizing enterocolitis and meningitis in neonates and infants globally. No data about the role of C. sakazakii as a cause of neonatal sepsis in North Africa is availale. Herein, we aimed to study the incidence of C. sakazakii in cases of neonatal sepsis, distribution in different food samples in Egypt, antimicrobial profile and the ability of the strains to form biofilm. Methods: A total of 100 positive blood cultures from cases of neonatal sepsis admitted to the neonatal ICU at Assiut University Children Hospital, Egypt were analyzed. In addition, 1100 food samples, including 400 powdered infant formula (PIF), 500 herbs and 200 water samples were screened for the presence of C. sakazakii. We evaluated the antimicrobial profile and the ability of the strains to form biofilms. Results: C. sakazakii was detected in 12 out of 100 cases of neonatal sepsis. The organism was also isolated from PIF, herbs and water in a percentage of 17.5%, 9.2% and 7.5 %, respectively. Regarding the antimicrobial sensitivity, all strains were resistant to ampicillin, amoxicillin, ampicillin/sulbactam, clindamycin, cephalothin and cephalexin. In addition, C. sakazakii strains showed the ability to form biofilms but with variable degrees of cell density. Conclusions: We reported, for the first time, cases of neonatal sepsis caused by the emerging life-threatening pathogen C. sakazakii in Egypt. The organism was also detected in contaminated PIF, herbs and water which may be a source of infection for neonates, especially in countries where natural herbs are widely used as an alternative medicine. Finally, collective efforts by parents, manufacturers of PIF and health-care personnel are essential to prevent serious infections caused by C. sakazakii, particularly in infants.